Regional Convergence and Divergence Tendencies in Europe: Concepts and Recent Developments - Sascha Sardadvar (European Regional Science Association (ERSA), 2010)
Recent empirical studies on regional economic growth have extended regressions on convergence to account for externalities and spatial dependencies. Most of these studies, however, set the focus on whether regional output levels display convergence trends and consequently tend to ignore persisting or widening disparities that may occur at the same time. This paper examines the simultaneous occurrence of regional convergence and divergence tendencies in Europe by applying a spatial econometric model specification that is derived from a neoclassical growth model. Depending on factor endowments and relative locations in space, divergence may occur within sub-groups of regions despite an overall observation of convergence. The observation area comprises 253 European regions of the EU and EFTA on the NUTS2 and equivalent level, with empirical results provided for an observation period from 2001 to 2007.
Keywords: 330